Efficacy of Silver Diamine Fluoride in Arresting Dental Caries in Primary Teeth in Patient Visiting Tertiary Hospital of Kathmandu - Gyawali, Namrata; Sundas , Sunanda; Sah, Barun Kumar; Dhakal, Neha (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Carious lesions can both be prevented and arrested using fluoride-based materials. This study was done to evaluate and compare the efficacy of silver diamine fluoride in arresting dental caries at different frequencies of applications. Methods This experimental study was conducted among ten preschool children of 3-5 years old with seventy-four active carious lesions taking teeth as a sample unit. Children were randomly allocated into two intervention groups: Group 1— application of 38% silver diamine fluoride solution atthree consecutive weeks and Group 2— three applications of 38% silver diamine fluoride solution at monthly interval. The time taken of caries arrest was recorded. Data were collected and entered in Microsoft Excel sheet and analysis was done in Statistical Package for the Social Sciences (SPSS) version 16. Results The mean time taken for caries arrest for Group II (57.20 days) was found to be statistically longer than Group I (21.54 days) (p-value < 0.001). As the mean time taken for caries arrest for Group I was shorter, the weekly application was found to have higher efficacy than the monthly application. Conclusions Efficacy of Silver Diamine Fluoride was found to be more in Group I (weekly application) compared to Group II (monthly application).